The Endless War on Anzac. - BENDLE, MERVYN (Quadrant Magazine, 2024)
The author shares his reflections about the Left's attempt to destroy the Anzac tradition and the Anzac Day. Topics discussed include personal characteristics exhibited by Australian soldiers at Gallipoli and on the Western Front during the First World War, the culture war against the Anzac based on the book "Anzac and Its Enemies: The History War on Australia's National Identity," and the phases of the strategy to destroy the Anzac which includes the war of position and the war of maneuver.